Surat-surat pilihan: q.s. al-fiil (105), al-humazah (104), al-ashr (103) dan at-takatsur (102), menulis huruf hijaiyah (terpisah dan bersambung) dan ghunnah, hadist tentang keutamaan belajar AL-QUR’AN (خيرُكُم مَن تعلَّمَ القرآنَ وعلَّمَه) - Rahmawati, Sherly (Maliki Interdisciplinary Journal, 2026)
This article discusses the core messages of four short chapters in the Qur’an, namely Surah Al-Fiil, Al-Humazah, Al-‘Ashr, and At-Takatsur, while also connecting them to the Prophet Muhammad’s ﷺ hadith regarding the virtue of learning and teaching the Qur’an. Each of these chapters conveys profound moral, spiritual, and social lessons that remain relevant as guidance for human life across all eras. Surah Al-Fiil emphasizes the greatness and power of Allah SWT through the story of Abrahah’s army of elephants that was destroyed by flocks of birds sent by Allah. This story serves as a reminder that human arrogance is meaningless before the might of Allah. Surah Al-Humazah condemns those who slander, mock, and hoard wealth arrogantly, warning of the terrifying punishment in Hutamah Hellfire that burns even the hearts. Surah Al-‘Ashr highlights the value of time, declaring that mankind is in loss except those who have faith, perform righteous deeds, encourage one another to uphold the truth, and persevere in patience. Meanwhile, Surah At-Takatsur warns against being distracted by worldly competition in wealth and pride, as every human will ultimately be held accountable before Allah for the blessings they enjoyed. In addition, this article reflects on the hadith of the Prophet ﷺ which states, “The best of you are those who learn the Qur’an and teach it.” This hadith affirms that a Muslim’s true excellence lies in their interaction with the Qur’an—reading it, understanding its meanings, practicing its teachings, and passing it on to others. Such engagement not only brings personal reward but also contributes to society by nurturing Qur’anic generations with noble character. Therefore, the combined teachings of Surah Al-Fiil, Al-Humazah, Al-‘Ashr, and At-Takatsur, along with the prophetic tradition, provide comprehensive guidance for attaining both worldly well-being and eternal salvation.